Intertemporal Competitive Equilibrium: An Empirical Study of Speculation - Miller, Ross M.; Plott, Charles R.; Smith, Vernon L. (Quarterly Journal of Economics, 1977)
Theory and hypotheses, 600.—Subjects and experimental design, 601.—Experimental results, 605.—Concluding remarks, 610.—Appendix 1: Instructions for market experiment 1, 610.—Appendix 2: Instructions, 615.—Appendix 3: Subject index and limit prices, 618.—Appendix 4: Contracts in experiment 1, and bids, offers, and contracts for experiment 2, 619.